Robotic Interventional Neuroradiology: Progress, Challenges, and Future Prospects - Ning, Shen; Chautems, Christophe; Kim, Yoonho; Rice, Hal; Hanning, Uta; Al Kasab, Sami; Meyer, Lukas; Psychogios, Marios; Zaidat, Osama O.; Hassan, Ameer E.; Masoud, Hesham E.; Mujanovic, Adnan; Kaesmacher, Johannes; Dhillon, Permesh S.; Ma, Alice; Kaliaev, Artem; Nguyen, Thanh N.; Abdalkader, Mohamad (Seminars in Neurology, 2023)
Advances in robotic technology have improved standard techniques in numerous surgical and endovascular specialties, offering more precision, control, and better patient outcomes. Robotic-assisted interventional neuroradiology is an emerging field at the intersection of interventional neuroradiology and biomedical robotics. Endovascular robotics can automate maneuvers to reduce procedure times and increase its safety, reduce occupational hazards associated with ionizing radiations, and expand networks of care to reduce gaps in geographic access to neurointerventions. To date, many robotic neurointerventional procedures have been successfully performed, including cerebral angiography, intracranial aneurysm embolization, carotid stenting, and epistaxis embolization. This review aims to provide a survey of the state of the art in robotic-assisted interventional neuroradiology, consider their technical and adoption limitations, and explore future developments critical for the widespread adoption of robotic-assisted neurointerventions.
Keywords: interventional neuroradiology; robotics; robotic-assisted neurointerventions; robotic endovascular interventions